The Role of the Human Factor in Construction Safety - A., Bayzakov A. (European Journal of Life Safety and Stability (2660-9630), 2021)
The purpose of this article is to examine the role of the human component in hazardous situations, the causes of dangerous situations, and their occupational features in order to prevent injuries and accidents in building operations.